(untitled) (Global Journal of Management and Business Research, 2019)
The financial markets need the availability of good information enables investors to choose the best alternatives available for the right price system, This view is supported by many researchers when they assert that the internal information is considered one of the main ingredients for an investor when making its decision shall be served as the main information for the investor in making his decision, and the foundation will build it all resolutions available in the market and traded investment and the time period for retaining each alternative. (Khalil, 2005) Jordan realized early the importance of foreign direct investment and its role in influencing the overall economic development through the funding of development projects and create jobs and increase competitiveness in foreign markets efforts.